2013
DOI: 10.1136/bmj.f6064
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to advance care planning in practice

Abstract: What are the benefits of advance care planning? Theoretically, the process can facilitate patient autonomy so that patients' future wishes can be carried out once they can no longer decide for themselves, 1 but evidence regarding real benefit is mixed. A controlled trial of the impact of combining improved communication about resuscitation preferences with information on prognosis found no improvement in the quality of end of life care. 12 Other authors have suggested that the wider advance care planning pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 42 publications
(36 reference statements)
3
151
0
7
Order By: Relevance
“…Evidence of its effectiveness is limited and conflicting. 4,137 Some studies have reported benefits. 128,[130][131][132]138,139 These tend to be based on surveys, and to focus on a comparative reduction in days and deaths in hospital and costs associated with care in the last year of life.…”
Section: 114mentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence of its effectiveness is limited and conflicting. 4,137 Some studies have reported benefits. 128,[130][131][132]138,139 These tend to be based on surveys, and to focus on a comparative reduction in days and deaths in hospital and costs associated with care in the last year of life.…”
Section: 114mentioning
confidence: 99%
“…Evidence of the nature, frequency and outcomes of ACP discussions remains limited and frequently conflicting. 4 However, it is apparent that ACP remains uncommon in most areas of professional practice and that both professionals and patients tend to avoid discussions they find difficult. [5][6][7][8][9][10][11][12][13][14] Patient and family responses to ACP and its effect on EOLC outcomes remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…with great interest. 1 In support of the lack of evidence that reducing blood pressure helps, the authors quote the POISE study, 2 stating that beta-blockers were used to reduce blood pressure preoperatively and the data suggested that it did more harm than good. POISE was not designed to test the effects of reducing blood pressure before surgery in hypertensive patients, but rather to assess whether introducing beta-blockade immediately prior to surgery and continuing it for 30 days reduced the risk of cardiac events in patients at risk of, or with, coronary artery disease, vascular disease, previous stroke, etc.…”
Section: Hypertension In Surgical Patients: the Role Of Beta-blockersmentioning
confidence: 99%